PERCEPTION OF HISTORY EDUCATION COLLEGE STUDENT ABOUT HISTORY EDUCATION PROGRAM STUDY (UNIVERSITY PGRI PALANGKARAYA CLASS OF 2014 CASE STUDY) - Sumiatie (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
Perception is a process that involves the inclusion of a message or information to the human brain. Through continuous human perception meneurs make contact with the environment. This relationship is done through the senses, the senses of sight, the listener, touch, taste and smell. The method used in this research is Qualitative. To obtain the data used participatory observation methods passive (passive participation), interview (in dept interview), study the documentation. To test the objectivity and validity of the data used source triangulation techniques and triangulation techniques. Triangulation means to get data from different sources with the same technique, while triangulation technique means researchers used data collection techniques vary to obtain data from the same data source. Data analysis was performed using analytical models of interaction (interactive analysis models) are components of data reduction and data presentation is done in conjunction with the data collection process. After the data is collected, the three components of the analysis (data reduction, data presentation, drawing conclusions) interact. The results showed that 1). History college student class of 2014 perception toward history education program study can be said good or positive. 2). Enthusiastic students in the form of inflammatory spirit obtained during the continuity of the learning process. 3). College interest inevitably arise when they have been registered as a college student of history education Program Study and ready for the college. 4). Background electoral history majors are not always coherent with the ideals of the college student.